Determination of Palladium in Precious Metal Waste by Sieve Conducted Two Syringes Pressurized Liquid Phase Microextraction (SCTS-PLPME) and Slotted Quartz Tube Flame Atomic Absorption Spectrometry (SQT-FAAS) - Gosterisli, Tugce Unutkan; Cesur, Buket; Tezgit, Ezgi; Bakirdere, Emine Gulhan; Keyf, Seyfullah; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2022)
Determination of palladium at trace levels in environmental samples is essential due to its harmful properties and threats to living organisms. Hence, a simple but efficient liquid-phase microextraction method is reported by sieve conducted two syringes pressurized liquid phase microextraction (SCTS-PLPME) and slotted quartz tube flame atomic absorption spectrometry (SQT-FAAS). The originality of this system is based on the elimination of disperser solvents that are used to increase the surface area of extractant. The high pressure created by the movement of syringe plungers results in efficient dispersion of the extractants in the sample solution. Parameters that affect the overall efficiency of the extraction method were carefully optimized. The limit of detection (LOD) and quantification (LOQ) under the optimum conditions were 6.0 and 20.0 mu g L-1, respectively. The developed method showed good linearity between 20 and 1000 mu g L-1, and provided a 25-fold enhancement in detection power compared to conventional FAAS. The optimized method was successfully used to determine the analyte in precious metal waste samples.
Keywords: Flame atomic absorption spectrometry (FAAS); liquid-phase microextraction; palladium; sieve conducted two syringes pressurized liquid phase microextraction (SCTS-PLPME; slotted quartz tube; PLATINUM-GROUP ELEMENTS; TRACE AMOUNTS; PRECONCENTRATION; SAMPLES; WATER; OPTIMIZATION; EXTRACTION; HEALTH; PD(II); DROP; Chemistry